Aliphatic, Cyclic, and Aromatic Organic Acids, Vitamins, and Carbohydrates in Soil: A Review - Valerie Vranova; Klement Rejsek; Pavel Formanek (The Scientific World Journal)
Organic acids, vitamins, and carbohydrates represent important organic compounds in soil. Aliphatic, cyclic, and aromatic organic acids play important roles in rhizosphere ecology, pedogenesis, food-web interactions, and decontamination of sites polluted by heavy metals and organic pollutants. Carbohydrates in soils can be used to estimate changes of soil organic matter due to management practices, whereas vitamins may play an important role in soil biological and biochemical processes. The aim of this work is to review current knowledge on aliphatic, cyclic, and aromatic organic acids, vitamins, and carbohydrates in soil and to identify directions for future research. Assessments of organic acids (aliphatic, cyclic, and aromatic) and carbohydrates, including their behaviour, have been reported in many works. However, knowledge on the occurrence and behaviour of D-enantiomers of organic acids, which may be abundant in soil, is currently lacking. Also, identification of the impact and mechanisms of environmental factors, such as soil water content, on carbohydrate status within soil organic matter remains to be determined. Finally, the occurrence of vitamins in soil and their role in biological and biochemical soil processes represent an important direction for future research.